A influência da atmosfera criada pelo ambiente do ponto de venda sobre o comportamento de compra: uma pesquisa exploratória sobre a pinkbiju unidade Metrô Paulista - Santos, Thiago Alves dos (2014)
This paper aims at identifying the influence of variables that make up the layout on the purchase behavior of the consumer, considering the object of this paper, the selling point, its place and retail of bijouterie and accessories. For this, based on a bibliographic search about purchase behavior, the selling point, through the exploratory analysis and an attitudinal instrument, along the collection of data, in order to draw a parallel between the variables that make up the layout of the store and purchase behavior of consumers. It was concluded that all the variables that constitute the layout of retail store influence the purchase behavior of the consumer, including the colors, the lighting and the visual and physical accessibility of the product